Space-Based Driven Approach to Hydrological Analysis of Prospective Watersheds and Dams for Sustainable Irrigation in Niger State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the hydrological characteristics of prospective watersheds in Niger State, Nigeria, using a space-based approach to support enhanced and sustainable irrigation agriculture. The methodology integrates climatic and hydrological data to develop a comprehensive, data-rich framework for water resource management within geo-hydrological units, supporting agricultural planning and environmental protection. The study employs statistical computation of land resources using Sentinel-2 imagery in Google Earth Engine, along with spatial analysis of hydrological systems using Digital Elevation Model (DEM) data for stream network analysis. A Multi-Criteria Decision Analysis (MCDA) was applied to identify potential reservoir sites, incorporating topography, stream order, catchment area, and slope as key criteria. Criteria weights were assigned using expert judgment and a pairwise comparison approach, with topography and stream order receiving the highest weights given their primary influence on water accumulation and flow routing.The study delineated twenty-two (22) prospective watersheds as geo-hydrological units, ranging in size from 675.77 km² to 12,358.8 km². The circularity ratios indicate that more than 55% of the watersheds have values between 0.4 and 0.5, suggesting irregular shape, moderate surface runoff, and high permeability, characteristics consistent with structural controls from remnant tectonic features in the underlying crystalline rocks. Multiple factors, including topography, land use, soil type, geology, and climate, influence the hydrological characteristics of these watersheds. Stream networks display a dendritic pattern flowing predominantly NE–SW, parallel to the Nigerian regional lineament, indicating structural control and confirming their role as conduits for groundwater recharge. The failed triple-arm rifting system responsible for the Niger and Benue river valleys and sedimentary basins has exerted significant structural influence on the region.Niger State has an agricultural land area of approximately 25,361.27 km², which accounts for more than 80% of the state's total land area, while water bodies cover 460.51 km², indicating substantial irrigation potential. The prospective water reservoirs identified in this study have the combined capacity to irrigate more than 22,000 km² of agricultural land. Specifically, the Shiroro and Zungeru Dams can irrigate 2,642.41 km² of agricultural land within their basins, while the Kainji and Jebba Dams have the capacity to irrigate approximately 7,000 km² and 4,000 km², respectively. The study recommends effective multi-sectoral collaboration, participatory planning, integrated management, and adaptive strategies to sustainably manage these prospective watersheds, with the overarching goal of balancing ecological, economic, and social needs through integrated land and water resource management in support of SDG 2 (Zero Hunger) and SDG 6 (Clean Water and Sanitation).